Post-Crisis Women’s Leadership Mediation: An Empirical Study at the University of Lampung - Ina Iriyana; Dian Kagungan; Devi Yulianti; Intan Fitri Meutia (Walidem Institute and Publishing, 2026)
Objective: This study analyzes the mediating mechanism of women's leadership in the transformation of post-crisis higher education governance based on a synthesis of literature and empirical findings from the University of Lampung. Identify the indirect pathways of women's leadership's contribution to institutional outcomes through strengthening organizational performance and institutional innovation. Theoretical Framework: Based on transformational leadership and authentic leadership that place value change, integrity, and the formation of a collective vision as the basis for organizational effectiveness. Literature Review: The literature shows that women's leadership is characterized by collaborative, participatory, and relational leadership that strengthens social cohesion, symbolic legitimacy, and the adaptive capacity of organizations in a post-crisis context. Method: Qualitative research with a systematic literature review and thematic analysis of 45 publications from 2015–2025, combined with reflective interpretation of empirical findings from the University of Lampung as an anchor case. Results: The contribution of women's leadership does not occur directly, but is mediated through three main channels, namely relational (institutional cohesion and trust), structural (organizational performance and institutional innovation), and cultural (value transformation and governance legitimacy). Implications: The findings emphasize the importance of strengthening the capacity of organizational systems based on social relations, leadership distribution, and internalization of integrity values ​​to support the restoration of sustainable institutional legitimacy. Novelty: This study formulates a conceptual model of post-crisis women's leadership based on systemic mediation mechanisms that integrate relational, structural, and cultural dimensions as the foundation for the transformation of public organizational governance.